2012
DOI: 10.1007/s10815-012-9775-1
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates and bisphenol do not accumulate in human follicular fluid

Abstract: In reproductive age women undergoing infertility treatments there is little transfer or accumulation of phthalates, phthalate metabolites or bisphenol A into the microenvironment of the human preovulatory oocyte and the levels are not clinically significant. Further investigation of phthalate and bisphenol A accumulation in vivo in human follicular fluid may not be productive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 29 publications
2
50
2
Order By: Relevance
“…Furthermore, animals and plants accumulate DEHP in the body after contact . Several studies have shown that DEHP exposure is associated with testicular, mammary gland, liver, renal, and ovarian dysfunctions . These effects were found when exposure occurred at different times throughout the lifetime from the prenatal to the adult period, and may possibly involve different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, animals and plants accumulate DEHP in the body after contact . Several studies have shown that DEHP exposure is associated with testicular, mammary gland, liver, renal, and ovarian dysfunctions . These effects were found when exposure occurred at different times throughout the lifetime from the prenatal to the adult period, and may possibly involve different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is estimated that the range of daily human exposure to DEHP is between 3-30 μg/kg/day [3, 4]. Continuous, daily exposure to DEHP is a major concern because DEHP and its metabolite mono(2-ethylhexyl) phthalate (MEHP) have been identified in human blood samples [5, 6], urine samples [1, 5-9], amniotic fluid samples [10-12], cord blood samples from newborns [13, 14], breast milk samples [6], and in ovarian follicular fluid samples tested [15], indicating the ability of these chemicals to reach the ovary.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the estimated range of daily human exposure to DEHP is 3-30 lg/kg/day [3,4]. Exposure to DEHP represents a public health concern because DEHP and its metabolite, mono(2-ethylhexyl) phthalate (MEHP), have been identified as top contaminants in human tissues such as blood [5,6], urine [1,[5][6][7][8][9], amniotic fluid [10][11][12], umbilical cord blood [13,14], breast milk [6], and ovarian follicular fluid [15]. Important from a toxicological standpoint, it is hypothesized that the toxicity of DEHP is mediated by the bioactive metabolite MEHP in many organ systems, including the ovary [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%